The Use of Market Value Added in Performance Evaluation of Investment Centres - Nita, Bartłomiej (Zastosowanie rynkowej wartości dodanej w ocenie dokonań ośrodków odpowiedzialności za inwestycje, 2011)
The paper deals with the use of market value added in performance evaluation of investment centres. In the first part the essence of market value added is briefly depicted. Furthermore, the major value creation drivers affecting MVA are identified: return on sales, capital requirements in an investment centre, weighted average cost of capital and divisional growth. In the second part the relationships among these factors are examined and finally their impact on market value added generated in an investment centre is analyzed.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 97-106
Keywords: investment centre; responsibility accounting; market value added